Analisis Partisipasi Politik Ulama Dalam Pilkada Serentak di Kabupaten Polewali Mandar - M Amin; Farida Utami; Fitriani Sari Handayani Razak (FisiPublik: Jurnal Ilmu Sosial dan Politik, 2020)
This article discusses the political participation of ulama in the Simultaneous Local Election in Polewali Mandar Regency. In the political tradition in Polewali Mandar, the main religious figure of Ulama is the central concern of the people in that place. This is because the Ulama become a figure who is heard and followed by their words and choices, so that every candidate for regent and deputy regent who will participate in the elections will first make a political visit to the charismatic Ulama in Polewali Mandar. This type of research used in this study is a qualitative research with a descriptive approach. An interesting thing that was obtained in the condition of Simultaneous Local Election in Polewali Mandar was the Political Participation of Ulama Voters' in the regional head election in Wonomulyo Subdistrict, Polewali Mandar Regency. Active participation, scholars are actively involved in determining the district head election process, because the election of the district head is an important issue that is in the interests of the general public, and scholars are considered an example of a true leader voter, and scholars are considered by the community as mediators in the event of a conflict of interest between supporters